O popular e o erudito em Theodor Adorno: a situação da música no contexto da indústria cultural - Fabiano Leite França (2014)
The objective of this research is to uncover the identity and differences of what Theodor W. Adorno (1903-1969) understands by popular music and classical music, from the dialectical juxtaposition of the two spheres of music, contemplating the relationships that develop between these spheres itself as well as the relationships that popular music and classical music have with society, considering the advent of the culture industry as the mediating place of these relationships. To carry out this project, necessary will be done, firstly, examine how the concept of cultural industry, placing it as a premise and foundation of discussion about music. Then, the proposal is to define the structural differences of popular music and classical music in Adorno's conception, emphasizing the issue of standardization as a phenomenon resulting from the capitalist mode of production absorbed by the culture industry. The analysis of this phenomenon will clarify and distinguish the characteristics of hearing that each of the two spheres of music requires, centering on the concept of pseudo-individuation as a necessary subjective effect of standardization. Finally, the concepts of commodity fetish and the regression of listening, to similar effect (and respectively) to the concepts of standardization and pseudo-individualization will lead to clarification of the situation of popular music and classical music, from the analysis of its production and consumption in the context of the cultural industry.